2021
DOI: 10.1177/08902070211012931
|View full text |Cite
|
Sign up to set email alerts
|

Individual and experiential predictors of character development across the deployment cycle

Abstract: How soldiers adapt to and change in response to the deployment experience has received a great deal of attention. What predicts which soldiers are resilient and which soldiers decline in character strengths across the deployment transition? We examined this question in two analyses drawing from the same data source of soldiers deploying for the first time (Analysis 1: N = 179,026; Analysis 2: N = 85,285; Mage = 24.6–24.7 years old, SD = 4.87; 66.5–66.9% White). Specifically, we examined how individual (e.g. so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…Our findings align with prior research that showed stability in a variety of outcomes following an event (Milojev et al, 2014;Chopik et al, 2021Chopik et al, , 2022Blackie and McLean, 2022;Fassbender et al, 2022;Forgeard et al, 2022;Jayawickreme et al, 2022;Reitz et al, 2022) and thus provide further evidence that stability in well-being is the more typical response to major life events (e.g., Infurna et al, 2022;Laceulle et al, 2022;Serrano et al, 2022). Furthermore, in line with growing longitudinal evidence, our results fail to detect evidence for possible post-traumatic growth following major life stressors, insofar as such growth might relate to a broad range of different aspects of well-being (Davis et al, 2021;Rakhshani and Furr, 2021;Dorfman et al, 2022;Infurna et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings align with prior research that showed stability in a variety of outcomes following an event (Milojev et al, 2014;Chopik et al, 2021Chopik et al, , 2022Blackie and McLean, 2022;Fassbender et al, 2022;Forgeard et al, 2022;Jayawickreme et al, 2022;Reitz et al, 2022) and thus provide further evidence that stability in well-being is the more typical response to major life events (e.g., Infurna et al, 2022;Laceulle et al, 2022;Serrano et al, 2022). Furthermore, in line with growing longitudinal evidence, our results fail to detect evidence for possible post-traumatic growth following major life stressors, insofar as such growth might relate to a broad range of different aspects of well-being (Davis et al, 2021;Rakhshani and Furr, 2021;Dorfman et al, 2022;Infurna et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…The importance of assessing longitudinal (positive) change following major life events is evident in studies that have tracked outcomes across time. Such studies show remarkable stability pre- and post-event across a range of outcomes, including empathy, life satisfaction, religiosity, and personality ( Milojev et al, 2014 ; Chopik et al, 2021 , 2022 ; Blackie and McLean, 2022 ; Dorfman et al, 2022 ; Fassbender et al, 2022 ; Forgeard et al, 2022 ; Jayawickreme et al, 2022 ; Reitz et al, 2022 ). Thus, stability or declines in functioning appear to be the more typical response to adversity, with growth or positive change being much less prevalent than suggested by prior cross-sectional research ( Frazier et al, 2009 ; Davis et al, 2021 ; Rakhshani and Furr, 2021 ; Gander and Wagner, 2022 ; Infurna et al, 2022 ; Laceulle et al, 2022 ; Serrano et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the papers in this issue do not show positive personality change as a ubiquitous outcome of adversity, many papers identified key individual differences that predicted adaptive responses in the aftermath of adversity. For example, Chopik et al (2022) replicated their past research and identified two classes of change in character strengths among newly deployed US military personnel. Notably, and similar to the papers previously described, neither of the two classes represented a profile of personality growth from before deployment to 3 years afterward.…”
Section: A Personality Science Approach To the Study Of Post-traumati...mentioning
confidence: 78%
“…We similarly observed this in the trait of agreeableness, suggesting that while positive personality trait change may not be ubiquitous, there are individual differences for researchers to explore. Thus, methodological approaches that aim to identify the sub-groups that show a PTG trajectory and explore predictors of membership to this trajectory (Chopik et al, 2022) present one possible direction that researchers could take to further understand for whom and why PTG occurs.…”
Section: Discussionmentioning
confidence: 99%